Three-dimensional measurement method based on the singular operator and the shortest path search technique - Wang, Yongliang; Sun, Xiaoming; Duan, Yan; Chen, Yan (Frontiers in Physics, 2023)
Coded structured light plays a crucial role in the field of noncontact three-dimensional measurement. To improve the accuracy, we propose a novel method based on shortest path search and edge and central singular operator, which is able to detect the edge of Gray code and locate its line shift fringes more accurately. Starting from the patterns of the Gray code edge and the center of the line shift strip, we develop the corresponding singular operators and hence the cost function. The Euler distance is used as the distance condition for the adjacent key points, which are located by the fast-marching algorithm. We propose a method to compute the graph with minimum energy by finding the shortest path. The shortest path was automatically calculated and found both the edge of the Gray code and the center of the bar stripe accurately.